Temporal distribution of cyanobacteria in the coast of a shallow temperate estuary (Río de la Plata): some implications for its monitoring - Sathicq, María Belén (2014)
The aim of this study was to analyze the temporal distribution of phytoplanktonic cyanobacteria in a site located in the freshwater tidal zone near the extraction point for the drinking water supply. Samples were taken considering three timescales as follows: hours, days, and weeks, during the period of highest development of cyanobacteria. The phytoplankton density, microcystin concentration (LR, RR, YR), and chlorophyll-a were related to meteorological variables (wind and temperature), tidal high, and physical-chemical variables (nutrients, pH, conductivity, light penetration). The results obtained in this study showed that the variables that primarily modulate the temporal distribution of cyanobacteria were temperature, pH, light penetration, conductivity, and nutrients (particularly NO₃ ⁻ and NH₄⁺), while the winds and tide had a secondary effect, only evidenced at an hourly scale. Therefore, this timescale would be the most suitable for monitoring cyanobacterial populations, when the amount of cyanobacterial cells exceeds the alert I level proposed by the World Health Organization. This recommendation is particularly important for the water intake zones in Rio de la Plata, which are vulnerable to the damage generated by cyanobacteria on the water quality.